Effects of embedded multimedia in directed reading lessons on student engagement and media analysis - Verzo, Emmanuel B. Jr. (2017)
Access online through this link: https://journals.upd.edu.ph/index.php/ali/article/view/5783
Keywords: Student engagement; Assessment of education; Media literacy